(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article highlights the adverse effects of not breastfeeding on both the mother and the infant. It extensively covers the topic based on global statistical data, scientific research, and expert analyses. The impact of breastfeeding on the infant’s health, development, and the mother’s well-being is discussed in detail. The paper provides an in-depth understanding of the decline in breastfeeding rates in modern society and its consequences.